Optimization of Social Capital in Financial Management and Education Quality of YPKT Christian Schools - Isak Pasulu; Mey Enggane Limbongan; Astriwati Biringkanae (Journal of Economics and Management, 2026)
This research investigates the strategic role of social capital in enhancing educational quality in faith-based institutions, specifically the YPKT school network. Amid increasing financial volatility in private schools, this study proposes a structural model integrating social capital, financial management, and stakeholder collaboration. Employing a mixed-methods approach, the research initially used qualitative inquiry (FGDs and interviews) to identify indigenous values, such as Sipamanda, followed by quantitative validation using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 155 managerial-level respondents. The empirical results demonstrate that optimized social capital significantly predicts educational quality, both directly and through the mediating pathways of transparent financial management and robust stakeholder synergy. The model explains 61.2% of the variance in quality outcomes, highlighting that social trust effectively reduces agency costs and mobilizes community-led endowment funds. These findings suggest that for religious-based foundations, institutionalizing social networks into formal managerial frameworks is a prerequisite for achieving long-term fiscal resilience and pedagogical excellence. The study provides a strategic roadmap for school administrators to transform intangible communal assets into tangible institutional outcomes.